Konsep Moderasi Beragama dalam Pendidikan Islam: Studi Literatur atas Ayat-Ayat Al-Qur'an dan Hadis - Agus Mufaridah; Hawwin Huda Yana; Ahmad Mubaidilah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The concept of religious moderation in Islamic education becomes very relevant to form individuals who are able to live harmoniously in a multicultural society. However, there are still few studies that deeply examine how the principles of religious moderation reflected in the verses of the Qur'an and Hadith can be integrated in Islamic education. This study aims to analyze the concept of religious moderation in the Qur'an and Hadith and its implications in Islamic education. The method used is library research by analyzing the relevant texts of the Qur'an and Hadith, and connecting them with the theory of Islamic education. The results show that religious moderation, manifested in the balance between rights and obligations and the avoidance of extremism, can be a strong basis for developing a more inclusive and tolerant Islamic education curriculum. Moreover, the application of these moderation values has the potential to reduce social polarization and promote harmony in society. This research makes an important contribution to the development of moderation-based Islamic education theory and opens up opportunities for further research involving empirical approaches and the implementation of a religious moderation-based curriculum. The social and ethical implications of this research also demonstrate the importance of using digital technology in supporting the dissemination of religious moderation values to create a more peaceful society.